Development of Life and Career Skills Scale for University Students - Dogru, Mustafa; Celik, Melahat; Koca, Ceren; Tongal, Aysegul (Asian Journal of Contemporary Education, 2022)
The purpose of this study is to develop a valid and reliable scale to determine the life and career skills of university students. 396 university students in Turkey who look for work have participated in Exploratory Factor Analysis (EFA) and also data were collected from 439 students for Confirmatory Factor Analysis (CFA). According to the result of the analysis, 4-factor scale consisting of 20 items was obtained. The Cronbach Alpha Coefficient was calculated to reveal the internal consistency of the scale and it was found to be 0.84. According to the result of CFA, fit indexes were calculated as X2 / df = 3.56, NFI = 0.94, NNFI = 0.95, RFI = 0.93, CFI = 0.96, GFI = 0.88, AGFI = 0.85, SRMR = 0.073, IFI = 0.96. The life and career skills of students studying at universities were measured by "Life and Career Skills Scale" developed by the researchers.